MERAWAT AKAR, MENUMBUHKAN RASA: GELAR BUDAYA SEBAGAI WAHANA MENJAGA WARISAN LELUHUR - Windari; Wahyuni, Ruslina Dwi; Nuranto (Inisiasi, 2025)
This community service activity aims to foster awareness and participation of the community in preserving local cultural heritage through the organization of the Gambirmanis Village Cultural Festival in Pracimantoro District. The program is implemented using an Asset-Based Community Development (ABCD) approach, focused on the strengths, potential, and assets that the community already possesses. The implementation stages include Discovery, Dream, Design, Define, and Destiny, involving traditional leaders, local artists, youth groups, MSME actors, and the village government. The results of the activities indicate that the ABCD approach can encourage the community to recognize and optimize the socio-cultural assets they possess. Cultural Festivals have become an effective platform to strengthen local identity, foster pride in ancestral heritage, and strengthen social ties across generations. Based on the implementation and evaluation results, it is recommended that Cultural Festivals be established as an annual routine agenda in the village, cultural groups be formed as drivers of traditional arts preservation, and digital documentation be developed to maintain the continuity of intangible heritage. Collaboration among the community, village government, and universities also needs to be continuously strengthened to support the sustainable development of local cultural potential. Thus, Gambirmanis Village can become a model of an independent, characterful, and competitive cultural village through the preservation of ancestral heritage.